2007
DOI: 10.1002/art.22746
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the p38 MAP kinase pathway is dysregulated in HLA–B27–expressing human monocytic cells: Correlation with HLA–B27 misfolding

Abstract: Objective. To investigate the cause of the enhanced intracellular replication of Salmonella enteritidis in HLA-B27-transfected U937 human monocytic cells and the contribution of HLA-B27 heavy chain (HC) misfolding.Methods. U937 monocytic cell transfectants stably expressing pSV2neo resistant vector (mock), wildtype HLA-B27, or mutated HLA-B27 HCs with amino acid substitutions in the B pocket were differentiated, infected with S enteritidis, and treated with signaling pathway inhibitors or specific p38 small in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…Previously, several different theories were proposed to explain the role of HLA-B27 in the pathogenesis of ReA [4], [34]. Our earlier studies showed evidence that HLA-B27 influences the intracellular persistence of arthritis-triggering Salmonella within monocytes [6], [10]. These results support the hypothesis of ineffective elimination of microbes in the pathogenesis of ReA [35].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Previously, several different theories were proposed to explain the role of HLA-B27 in the pathogenesis of ReA [4], [34]. Our earlier studies showed evidence that HLA-B27 influences the intracellular persistence of arthritis-triggering Salmonella within monocytes [6], [10]. These results support the hypothesis of ineffective elimination of microbes in the pathogenesis of ReA [35].…”
Section: Discussionsupporting
confidence: 80%
“…The expression of transfected HLA-B27 and HLA-A2 was confirmed by flow cytometry always in new batches of the cells as before [10], [11]. The level of expression of the transfected molecules in U937 cells was similar to that of HLA-B51, one of the MHC class I molecules endogenously expressed by U937 cells.…”
Section: Resultsmentioning
confidence: 53%
“…Subsequent studies showed that mono-association of HLA-B27 transgenic rats with Bacteroides vulgatus in a germ-free environment was sufficient to re-establish colitis in these animals [22], [23]. A series of studies by Granfors et al have demonstrated marked effects of HLA-B27 on innate immunity and host defense in vitro , including effects on bacterial invasion of cells, intracellular persistence, intracellular signaling, and cytokine production [24][28]. Penttinen et al showed that HLA-B27-transfected monocytes had enhanced inflammatory responses to lipopolysaccharide found on bacterial cell walls [26], [29].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that bacterial replication is increased 38 and that the p38 MAP kinase pathway may be disrupted. 39 This most likely represents an intracellular or at least nonantigen-presenting effect of HLA-B27. 40 Experiments using site-directed mutants of HLA-B27 show that the biological effect correlates with heavy chain misfolding, but is not associated with acute UPR activation and therefore the molecular mechanism remains to be defined.…”
Section: Usual Unusual and Unique Features Of Hla-b27 And Their Potementioning
confidence: 99%